The flowers in your dustbin: Girls in the North American punk subcultures of the 1990s - Leblanc, Lauraine (Université Emory, 1997)
Girls in male-dominated youth subcultures confront ideologies of gender which remain largely invisible and often tacitly accepted in many women's everyday lives. Punk girls choose to construct their femininity within a highly male-dominated, "masculinist," context; girls are present in such youth subcultures, but the masculine definition of their norms problematizes their participation. Thus, punk girls struggle to accommodate female gender norms within subcultural identities which are deliberately coded as "masculine." Although young women in America encounter the norms of the female gender role on a daily basis, punk girls' negotiations between the norms of femininity and those of punk open these prescriptions to critical examination which they might not otherwise be accorded. In this dissertation, I explore accounts of punk girls' engagements with both mainstream and subcultural gender norms. In constructing this account of girls' lived experiences in the punk subculture, I rely primarily upon the phenomenology, or experiential narrative, of punk girls' everyday lives. I elicited these accounts within the context of conducting participant observation in the punk scenes of four North American cities (Atlanta, Montreal, New Orleans, and San Francisco) from 1993 to 1995, conducting ethnographic interviews with forty punk girls. In the following, I explore various facets of punk girls' engagements with gender norms, including punk girls' narratives of engagement with the subculture; the construction of punk as a discourse of masculinity; punk girls' stylistic, behavioral, and discursive reconstructions of femininity; punk girls' experiences of public harassment and sexual harassment, and their strategic responses to these. I argue that these girls use the punk subculture in order to carry out resistances to varied forms of gender oppression, thereby developing stronger self-concepts in the face of adversity.
https://search.libraries.emory.edu/catalog/990005217790302486
Keywords: 1900-1999; 1990-1999; amériques; approches et analyses; atlanta; discipline; ethnographie; genre; harcèlement sexuel; masculinisme; montréal; mémoires/thèses; nouvelle-orléans; patriarcat; philosophie; périodes historiques; régions géographiques; résistance; san francisco; sciences humaines; systèmes d'oppressions; thématiques; violences

La Voz de la mujer: periódico comunista-anárquico, 1896-1897 - Universidad Nacional de Quilmes (Universidad Nacional de Quilmes, 1997)
La Voz de la Mujer, La Voix de la femme en français, est le premier journal anarcha-féministe au monde. Publié en Argentine par un collectif de femmes dont la communiste libertaire Virginia Bolten, il compte neuf numéros, parus du 8 janvier 1896 au 10 mars 1897. (Wikipedia)
Disponible gratuitement en ligne https://www.marxists.org/espanol/tematica/kiosko/argentina/voz-de-la-mujer/index.htm
Keywords: 1800-1899; 1890-1899; amérique latine; amériques; approches et analyses; argentine; cours; droits des femmes*; histoire et politique; inégalités; justice sociale; lit3220; patriarcat; premier cycle; périodes historiques; rapports sociaux de sexe; ressource en ligne; régions géographiques; sexisme; systèmes d'oppressions; thématiques